2020
DOI: 10.2147/ott.s244699
|View full text |Cite
|
Sign up to set email alerts
|

<p>Circular RNA circLPAR3 Facilitates Esophageal Squamous Cell Carcinoma Progression Through Upregulating HMGB1 via Sponging miR-375/miR-433</p>

Abstract: Background: Circular RNAs (circRNAs) are critical regulators of many diseases, including esophageal squamous cell carcinoma (ESCC). A recent study has shown that circLPAR3 is highly expressed in ESCC, but its role and mechanism in ESCC are still unclear. Methods: The expression levels of circLPAR3, microRNA-375 (miR-375), miR-433, and high-mobility group box 1 (HMGB1) were measured by quantitative real-time polymerase chain reaction (qRT-PCR). The circular characteristic and localization of circLPAR3 were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…HMGB3 is involved in the progression of some cancers, such as esophageal squamous cell cancer, breast cancer and so on. 36 , 37 HMGB3 has been demonstrated to play an oncogene role in CRC. 38 miR-93 targeted regulated HMGB3 expression, and the repression effect of miR-93 on biological behavior of CRC cells could be counteracted by HMGB3 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB3 is involved in the progression of some cancers, such as esophageal squamous cell cancer, breast cancer and so on. 36 , 37 HMGB3 has been demonstrated to play an oncogene role in CRC. 38 miR-93 targeted regulated HMGB3 expression, and the repression effect of miR-93 on biological behavior of CRC cells could be counteracted by HMGB3 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers reported that circLPAR3 exerted a tumor‐promoting impact through upregulating MET via binding to miR‐198 in ovarian cancer 22 and esophageal squamous cell cancer 23 . Cheng et al indicated that circLPAR3 sponged miR‐433/miR‐375 and elevated HMGB1 expression, resulting in ESCC growth 24 . Fu et al suggested that circLPAR3 was overexpressed in OSCC samples and cell lines, and circLPAR3 silencing decreased xenograft tumor growth and facilitated cell apoptosis, restrained cell proliferation, stemness, and migration through repressing HMGB2 by liberating miR‐643 19 .…”
Section: Discussionmentioning
confidence: 99%
“…23 Cheng et al indicated that circLPAR3 sponged miR-433/miR-375 and elevated HMGB1 expression, resulting in ESCC growth. 24 Fu et al…”
Section: Discussionmentioning
confidence: 99%
“…Our further ChIP-qPCR assay validated the direct interaction between miR-375 and E2F1. Previously, miR-375 has been indicated to be regulated by circular RNA and long noncoding RNA (lncRNA) in ESCC and tongue squamous cell carcinoma, respectively [ 26 , 27 ]. However, there is little information concerning the interactions between miR-375 and transcription factors, which highlights the novelty of our research.…”
Section: Discussionmentioning
confidence: 99%